Factors associated with needle breakage of antegrade suture passer and effect of intratendinous remnant needle tip on clinical outcomes after arthroscopic rotator cuff repair - Seok Won Chung; Kyung-Soo Oh; Se-Young Ki; Jayoun Kim; Jong Pil Yoon; Joon Yub Kim (Acta Orthopaedica et Traumatologica Turcica, 2019)
Objective: The aim of this study was to evaluate factors associated with the needle breakage of antegrade suture passer and the effect of intratendinous remnant needle tip on clinical outcomes after rotator cuff repair. Methods: We retrospectively reviewed 283 patients (138 men and 145 women; mean age: 59.7 ± 9.3 years) who underwent arthroscopic repair for full-thickness rotator cuff tear. We evaluated the characteristics of 16 patients in whose needle tip had been broken and embedded and remained in the rotator cuff (remnant needle group) and compared them with the remaining 267 patients (control group). Afterwards, another 64 patients were selected from control group (1:4 matching) after propensity score matching (PSM). The groups were compared anatomically with MRI or ultrasonography and functionally (serial pain VAS and ROM; ASES, Constant, UCLA and SST scores) at a minimum follow-up of 1 year. Results: The remnant needle group showed preoperative thicker tendon (6.72 mm vs 5.33 mm, p = 0.047), higher tendinosis (mean grade, 1.88 vs. 1.43, p = 0.029), and more frequent delaminated tears (p = 0.035) compared with control group. When we compare the clinical outcomes after PSM, the initial pain VAS of the remnant needle tip group was higher up to 3 months (pain VAS: 4.13 ± 2.07 vs 2.48 ± 1.61 (p = 0.032) at 5 weeks and 3.79 ± 2.12 vs 2.25 ± 1.76 (p = 0.044) at 3 months), however the difference disappeared after 6 months postoperatively. In final evaluation, there was no significant differences in every outcome parameters (all p > 0.05). Conclusion: Breakage of the needle of the antegrade suture passer occurred more frequently in the thicker tendon, higher tendinosis, and delaminated tears. The retained broken needle tip was associated with higher pain scores during the early postoperative period, but revealed no difference in final outcomes by using PSM. Level of Evidence: Level III, Therapeutic Study Keywords: Rotator cuff repair, Antegrade suture passer, Needle breakage, Clinical outcome Level of Evidence: Level III, Therapeutic Study